Mindful Attention to Everyday Social Categorization - Russell Suereth (Spirituality Studies, 2023)
This article employs a mindful approach to social categorization, which often turns negative and leads to prejudice, discrimination, and hatred. The main focus is put on considering whether mindfulness can help resolve social categorization in our daily lives. Buddhist mindfulness is examined as a means against human biases that influence us to categorize people socially. Through mindfulness, our views and interactions with others can be more open and caring. The article employs a mindful methodology that focuses on openness and consideration of the research and its subjects and contributes to the current state of research by creating a greater awareness of the connection between mindfulness and social categorization in our everyday lives.